Serological and molecular frequency of Leishmania spp and Trypanosoma cruzi and associated factors in dogs with signs suggestive of trypanosomatid infection in Quintana Roo, Mexico - Salazar Grosskelwing, Enrique (2020)
A cross-sectional study was conducted with a sample of 40 dogs with clinical signs suggestive of infection by Leishmania spp and Trypanosoma cruzi in the municipality of Lázaro Cárdenas, Quintana Roo, Mexico. Blood, skin and bone marrow samples were taken. Indirect immunofluorescence (IFI) tests for detection of anti-Leishmania infantum and immunochromatic test for the detection of anti-Trypanosoma cruzi antibodies in serum were performed. In addition, molecular analyses were performed using PCR to detect Leishmania spp in bone marrow and skin and T. cruzi in bone marrow. Histopathological analyses of the skin and cytology of the bone marrow were carried out in search of lesions and trypanosomatid agents. The results showed that 3 (7.5%) and 6 (15%) dogs with anti-L. infantum and T. cruzi antibodies were detected, respectively. Molecular analyses detected 17 dogs positive for infection by T. cruzi (42.5%) and none for infection by Leishmania spp. Dogs with low body condition showed greater seropositivity to T. cruzi using Fisher’s exact test (p<0.05). Parasites of the genus Leishmania did not actively participate in the pathological processes of the animals; however, a high frequency of animals infected with T. cruzi was observed.